Formulation of a 2-in-1 Conditioner-Shampoo Containing Morus nigra Ethanolic Extract with Surfactant Combination - Octrysa Puspajelita; Tasya Alfina Lestari; Dita Fitriana; Lutfiah Lutfiah; Muhammad Agung Fauzi; Safira Nafisa (Journal of Natural Product for Degenerative Diseases, 2025)
Black mulberry (Morus nigra) is rich in flavonoids and anthocyanins with antioxidant and conditioning properties that can improve hair health. However, its incorporation into a stable 2-in-1 conditioner-shampoo formulation remains limited. This study aimed to formulate and evaluate the physical stability of conditioner-shampoo preparations containing M. nigra ethanolic extract at concentrations of 5%, 10%, and 15% w/w using sodium lauryl ether sulphate (SLES) and cocamidopropyl betaine (CAPB) as surfactant bases. Each formulation was prepared by gradual mixing of aqueous and surfactant phases, followed by the addition of conditioning agents and active extract. Physical characteristics—including organoleptic properties, homogeneity, pH, foam height, and viscosity—were evaluated before and after six cycles of a stability test at 4 °C and 40 °C. All formulas exhibited homogeneous brown appearance with peppermint aroma and acceptable foam stability. The initial pH decreased with increasing extract concentration (F1 = 6.74; F2 = 5.95; F3 = 3.97) and slightly decreased after cycling (F1 = 6.21; F2 = 5.84; F3 = 3.61). Viscosity values ranged from 44,000 to 70,000 mPas and decreased after temperature cycling, whereas foam height remained within acceptable limits (≈ 1.5–2.3 cm). Among the tested formulations, F2 (10% extract) showed the most balanced properties in terms of pH, viscosity, and foam stability. In conclusion, a 10% M. nigra ethanolic extract conditioner-shampoo demonstrated good physical stability and potential as a natural antioxidant and conditioning hair-care product.